Practical checklist for implementation of antifungal stewardship programmes. Issue 6 (30th June 2022) - Bienvenu, Anne-Lise; Pavese, Patricia; Leboucher, Gilles; Berger, Pierre; Roux, Sandrine; Charmillon, Alexandre; Foroni, Luc; Menotti, Jean; Lebeaux, David; Mayan, Rémi; Mondain, Véronique; Robin, Christine; et al.
Abstract : Introduction. Antifungal stewardship programmes are needed in healthcare facilities to limit the overuse or misuse of antifungals, which are responsible for an increase in antifungal resistance. Hypothesis/Gap Statement. Core recommendations for antifungal stewardship were published by the Mycoses Study Group Education and Research Consortium, while the Centers for Disease Control and Prevention (CDC) provided a Core Elements of Hospital Antibiotic Stewardship Programs checklist. The recommendations offer global core elements for best practices in antifungal stewardship, but do not provide a framework for the implementation of antifungal stewardship programmes in healthcare facilities. Aim. In line with the recommendations, it is of the utmost importance to establish a practical checklist that may be used to implement antifungal stewardship programmes. Methodology. The practical checklist was established by a national consensus panel of experts involved in antifungal stewardship activities. A preliminary checklist was sent to all experts. The final document was approved by the panel after discussion and the resolution of any disagreements by consensus. Results. The final checklist includes the following items: leadership support; actions to support optimal antifungal use; actions to monitor antifungal prescribing, use and resistance; and an education programme. Conclusion. This antifungal stewardship checklist offers opportunities for antifungal resistance containment, given that antifungal stewardship activities promote the optimal use of antifungals.